Perceptions of Early Childhood Parents Towards Integrated Islamic Kindergarten Educational Institutions - Qotrun Nada Nafiah; Amina Rosa Mumtaza Rafiq; Youssef Shawky ElbehairyThird (JOYCED: Journal of Early Childhood Education, 2022)
This study aims to determine the perspective of parents on integrated Islamic educational institutions in the midst of the rise of Educational Institutions that are currently competing to carry out integrative learning. This research uses an exploratory case study method with a qualitative approach digging deeper into how parents' perceptions of integrated Islamic educational institutions and the factors of issues that build perceptions. The data source used is 8 early age parents who live in Plembutan Village. The data collection technique used is the in-depth interview technique. Data analysis uses three stages, namely data reduction, presenting data, and drawing conclusions. The result of this research is that an integrated Islamic educational institution is seen as an educational institution with a good curriculum because it can combine religious science and science, is classified as elite, is synonymous with a group, and attracts the attention of parents enough to make it an alternative in choosing the best educational institution for their children. The impact of this research is expected to be an illustration for educational institutions, both integrated Islamic institutions and other institutions to improve the quality of education based on the results of parents' views.